RELATIONSHIP BETWEEN BANK CREDITS AND MACROECONOMIC FACTORS IN NIGERIA - Kayode David KOLAWOLE (International Journal of Social and Educational Innovation)
Credit risk management is a very difficult and complex task in the financial industry due to unpredictable nature of the macroeconomic factors coupled with the various microeconomic variables which are peculiar to the banking industry or specific to a particular bank. The paper attempts to determine the association between bank credits and macroeconomic factors. The study seeks twofold aims: First the paper shows the relation between performing credits and macroeconomic variables, such as Inflation rate, monetary policy rate, inflation rate, interest rate and exchange rate. Second, the paper shows the relation between non-performing credits and macroeconomic variables, such as Inflation rate, monetary policy rate, inflation rate, interest rate and exchange rate. For achieve the aim, the study applied a simple correlation framework to assess the direction and extent and test the significance of the relationship between the considered macroeconomic variables and both performing credits and non-performing credits. The findings detail the determinants of nonperforming and performing credits of commercial banks in Nigeria shall be beneficial to different stakeholders in the banking sector (Deposit Money Banks and micro finance banks), monetary authority (Central Bank of Nigeria) and researchers. The findings shall also be used as definite inputs in developing regulatory standards regarding the lending policies of Deposit Money Banks in Nigeria. This study shall sensitize the deposit money bank management to give due emphasis to the management of these identified variables and provide them with further understanding of activities that can enhance their loan performance.